(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Peripheral intravenous (IV) cannulation is essential for administering medications in neonates but often has a short lifespan, leading to repeated procedures and increased risk of complications. The effectiveness of limb splinting in extending the dwell time of IV cannulae remains to be debated, with inconsistent findings reported in the literature. This study aimed to evaluate the impact of limb splinting on the lifespan of IV cannulae in neonates and to compare the incidence of associated. Methods: A randomized controlled trial was conducted. A total of 248 cannulations were randomized into two groups: 123 received IV cannulation with limb splinting and 125 without splinting. The primary outcome was the dwell time of the IV cannula, measured from insertion to removal. Secondary outcomes included the frequency of complications such as extravasation, accidental dislodgment, and leakage. Data were analyzed using SPSS version 26, with statistical significance at p<0.05. Results: The mean dwell time of IV cannulae was significantly longer in the splinted group (37.64 ± 14.48 hours) compared to the non-splinted group (31.33 ± 11.49 hours, p=0.005). Extravasation was the most common cause of cannula removal, observed in 45.2% of the splinted group and 39.1% of the non-splinted group. Conclusion: Limb splinting significantly increases the lifespan of IV cannulae in neonates, potentially reducing the need for repeated cannulations and associated complications. Further research is recommended to explore additional factors influencing the effectiveness of splinting.